Glycemic control and prostate antigen levels in individuals with diabetes based on NHANES data - Xiao Huo; Zhi Wang; Nan Huang; Jie Zhang (Scientific Reports)
Abstract The relationship between diabetes and prostate-specific antigen (PSA) levels is complex, with potential implications for prostate cancer screening. This study examined the association between glycemic control and total PSA (tPSA) levels in patients with diabetes. We analyzed data from the 2001–2010 NHANES to assess the relationship between glycated hemoglobin (HbA1c) and tPSA in adults with diabetes, categorizing HbA1c as < 7% (good glycemic control) or ≥ 7% (poor glycemic control). Multivariable regression models were used, adjusting for key demographic, clinical, and lifestyle factors, including age, race/ethnicity, marital status, body mass index (BMI), smoking status, alcohol use, hypertension, coronary artery disease (CAD), and insulin use. Adjustments for multiple comparisons were considered using the Bonferroni correction, and missing data were handled using multiple imputation. Participants with poor glycemic control were younger, less likely to be married or partnered, and had higher rates of insulin use but lower hypertension incidence than those with good glycemic control (P < 0.05). The median tPSA level was greater in the good control group (1.10 ng/mL vs. 0.90 ng/mL; P = 0.0014). Multivariate analysis revealed no overall association between HbA1c and tPSA (β = -0.022, P = 0.917). However, significant inverse associations were observed across subgroups, including those aged ≤ 59 years (β = -0.71, P = 0.033), married individuals (β = -0.55, P < 0.001), participants without CAD (β = -0.49, P = 0.015), and insulin users (β = -0.80, P = 0.031). Although no significant overall association was found between glycemic control and tPSA levels, subgroup analyses revealed an inverse relationship between HbA1c and tPSA in younger individuals (≤ 59 years), insulin users, and those without CAD. These findings suggest that glycemic control may have subgroup-specific effects on prostate health in individuals with diabetes.